Influence of Different Kinds of Plant Fibers on the Curing Kinetics of Epoxy Resin - Yeng-Fong Shih; Jia-Yi Xu; Nian-Yi Wu; Ting-Yuan Ou; Saprini Hamdiani (Universitas Gadjah Mada, 2022)
The curing kinetics of the epoxy resin crosslinked by an anhydride hardener with and without plant fibers was investigated. The epoxy composites containing modified pineapple leaf fiber (EASF), banana fiber (EBSF), and bamboo chopsticks fibers (ECSF) were analyzed by non-isothermal differential scanning calorimetry (DSC) technique. Dynamic methods were used to predict the total heat of reaction of the epoxy resin and its activation energy based on the methods of Kissinger and Ozawa. The results showed that, at a low heating rate (5 °C/min), the ΔH of the pure epoxy, EASF, EBSF, and ECSF were 326.2, 307.6, 295.6, and 366.6 J/g, respectively. The curing rate increased, and the activation energy was decreased due to the catalytic role of hydroxyl groups of plant fibers. Based on Kissinger and Ozawa methods, the calculation of activation energy for pure epoxy was 70.08 kJ/mol and 73.21 kJ/mol, EBSF was 68.07 kJ/mol and 71.41 kJ/mol, ECSF was 60.11 kJ/mol and 63.87 kJ/mol, and EASF was 58.71 kJ/mol and 62.49 kJ/mol. The activation energy for the three kinds of epoxy composite modified fibers was less than pure epoxy resin due to the gel effect resulting from the higher viscosity, faster curing rate, and steric hindrance.